Optimizing spectral quality with quantum dots to enhance crop yield in controlled environments - Charles H. Parrish (Nature Portfolio, 2021)
Parrish et al. demonstrate the modification of an incoming solar spectrum through downconversion of high energy UV/blue photons into orange/red photons using luminescent quantum dot films, leading to improved growth of leaf vegetables. Such technology can improve greenhouse productivity while reducing energy costs and can be useful to realize self-sustaining human settlements beyond Earth.